Risk of dementia associated with psychotic disorders in later life: the health in men study (HIMS). Issue 2 (22nd March 2018) - Almeida, Osvaldo P.; Ford, Andrew H.; Hankey, Graeme J.; Yeap, Bu B.; Golledge, Jonathan; Flicker, Leon
Abstract: Background: Recent research has identified several potentially modifiable risk factors for dementia, including mental disorders. Psychotic disorders, such as schizophrenia and delusional disorder, have also been associated with increased risk of cognitive impairment and dementia, but currently available data difficult to generalise because of bias and confounding. We designed the present study to investigate if the presence of a psychotic disorder increased the risk of incident dementia in later life. Methods: Prospective cohort study of a community-representative sample of 37 770 men aged 65–85 years who were free of dementia at study entry. They were followed for up to 17.7 years using electronic health records. Clinical diagnoses followed the International Classification of Diseases guidelines. As psychotic disorders increase mortality, we considered death a competing risk. Results: A total of 8068 (21.4%) men developed dementia and 23 999 (63.5%) died during follow up. The sub-hazard ratio of dementia associated with a psychotic disorder was 2.67 (95% CI 2.30–3.09), after statistical adjustments for age and prevalent cardiovascular, respiratory, gastrointestinal and renal diseases, cancer, as well as hearing loss, depressive and bipolar disorders, and alcohol use disorder. The association between psychotic disorder and dementia risk varied slightly according to the duration of the psychotic disorder (highest for those with the shortest illness duration), but not the age of onset. No information about the use of antipsychotics was available. Conclusion: Older men with a psychotic disorder have nearly three times greater risk of developing dementia than those without psychosis. The pathways linking psychotic disorders to dementia remain unclear but may involve mechanisms other than those associated with Alzheimer's disease and other common dementia syndromes.